Multiphysics simulation of pulsed cold plasma arc rotation for enhanced hydrogen harvesting. (7th December 2017) - Wu, Minxiang; Pacheco, Jose; Cosoroaba, Eva; Fahimi, Babak
Abstract: Pulsed cold plasma reforming is a novel method to harvest hydrogen from hydrocarbons. The harvested hydrogen can feed a fuel cell for distributed generation of electricity in a stationary or mobile platform. The cold plasma arc is generated by a pulsating high voltage waveform. The arc rotates in the magnetic field caused by a ring permanent magnet, thus increasing the collision area between the arc and the fuel. Due to the difficulties of measurement of plasma properties such as ion and electron temperature without disturbing the plasma, multiphysics simulation is a key step in the design of electrodes, thereby increasing the hydrogen harvest rate in the syngas. In this paper, a 3D multiphysics simulation including fluid dynamics, thermal response, and electromagnetic fields has been carried out to assist in selection of the permanent magnet. Experiments were carried out to verify the simulation results. The 3D multiphysics simulation is demonstrated to be an effective tool to assist in the design of the reformer. The hydrogen harvest rate has been improved from 58.7% to 67.8% with the introduction of the magnet. Highlights: A 3D multiphysics simulation of pulsed cold plasma arc rotation is proposed. The 3D multiphysics simulation is demonstrated as an effective tool to assist in the design of the reformer. The hydrogen harvest rate improves with the introduction of the magnet.